Kisah Wahyu Pertama Nabi Muhammad SAW: Awal Munculnya Islam di Jazirah Arab Abad ke-7 Masehi: Awal Munculnya Islam di Jazirah Arab Abad ke-7 Masehi - Mahlaini Azizah Harahap; Syarfira Syarfira; M. Al-Aziz Akbar; Hudaidah Hudaidah; Tyas Fernanda (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the event of the first revelation descending upon Prophet Muhammad SAW in the Cave of Hira as the starting point for the birth of Islamic civilization. The background of this research stems from the social and spiritual conditions of pre-Islamic Arab society, which was in the era of ignorance, characterized by idol worship, social inequality, and the loss of human values. The purpose of this research is to reconstruct the historical, theological, and philosophical meanings of the first revelation and relate them to the relevance of educational and moral values in the modern context. The method used is a qualitative study with a descriptive-analytical approach, utilizing primary and secondary literature from interpretive sources, historical texts, and scientific journals. The research results indicate that the command